2020
DOI: 10.14434/hindsight.v51i4.31557
|View full text |Cite
|
Sign up to set email alerts
|

History and Current Status of Optometric Education in Africa

Abstract: Over the last decade, 16 new optometry programs have been established across Africa and there are efforts to set up additional training institutions in the future. Also, existing optometry programs are undergoing modifications to offer an international standard of optometric education and training. This paper focuses on the history and further assesses the current status of optometric education on the continent of Africa. Additionally, optometric education in Africa is compared to North American training progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Optometrists in both Nigeria and Ghana are licensed to provide comprehensive primary eye-care services, such as refractive error correction, contact lens fitting, pediatric vision and binocular vision anomaly management, diagnosis and management of disease in the eye, and the rehabilitation of conditions of the visual system [ 20 , 24 , 28 , 29 ]. Currently, only in both countries do optometrists in Africa complete a six year undergraduate professional Programme leading to the Doctor in Optometry degree [ 20 , 28 ], which empowers them to provide general eye care including the glaucoma diagnosis and other eye diseases. Presently, there are two optometry schools in Ghana [ 30 ] and seven in Nigeria [ 31 ] all offering the OD degree.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Optometrists in both Nigeria and Ghana are licensed to provide comprehensive primary eye-care services, such as refractive error correction, contact lens fitting, pediatric vision and binocular vision anomaly management, diagnosis and management of disease in the eye, and the rehabilitation of conditions of the visual system [ 20 , 24 , 28 , 29 ]. Currently, only in both countries do optometrists in Africa complete a six year undergraduate professional Programme leading to the Doctor in Optometry degree [ 20 , 28 ], which empowers them to provide general eye care including the glaucoma diagnosis and other eye diseases. Presently, there are two optometry schools in Ghana [ 30 ] and seven in Nigeria [ 31 ] all offering the OD degree.…”
Section: Methodsmentioning
confidence: 99%
“…The study also identified the factors affecting the diagnosis of glaucoma among respondents. Although Nigerian and Ghanaian optometrists are the only African countries with the highest level of optometric education in Africa and the optometrists in these countries practice at the World Council of Optometry competency level four [ 20 ] which includes provision of glaucoma care; they may not be deliberately managing glaucoma with the preferred patterns of practice in mind. This study will provide evidence on the level of glaucoma diagnostic practice among optometrists from the region to inform planning, areas of practice improvement and sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Some 80% of the SSA population uses traditional medicine, and although not backed up by scientific published knowledge, it is a fascinating field for health research [71]. The practice of folk/traditional, complementary and alternative medicines for NCDs and mental disorders in health care of SSA patients is a factuality but still not researched in depth [72], [73], [81].…”
Section: The Thriving Challenges Of Non-communicable Diseasesmentioning
confidence: 99%
“…9 A milestone event for the profession took place in 2022 when the first ever scope of practice for optometrists in Kenya was published 9 and registration of practicing optometrists through a regulatory board – Kenya Health Professions Oversight Authority (KHPOA) was initiated. These suggest that although optometry training in Africa began nearly a century ago, 10 in Kenya, the profession is still in its infancy, but evolving. The majority of the optometrists are registered with the Optometry Association of Kenya (OAK), founded in 2009.…”
Section: Introductionmentioning
confidence: 99%